Rethinking the effects of immigration on wages - Gianmarco I. P. Ottaviano; Giovanni Peri (University of California, Department of Economics, 2006)
This paper asks the following important question: what was the effect of surging immigration on average and individual wages of U.S.-born workers during the period 1990-2004? Building on section VII of Borjas (2003) we emphasize the need for a general equilibrium approach to analyze this problem. The impact of immigrants on wages of US born workers can be evaluated only by accounting carefully for labor market and capital market interactions in production. Using such a general equilibrium approach we estimate that immigrants are imperfect substitutes for U.S.-born workers within the same education and experience group (because they choose different occupations and have different skills). Moreover, accounting for reasonable speed of adjustment of physical capital we show that most of the wage effects of immigration accrue to native workers already within a decade. These two facts, overlooked by the previous literature, imply a positive and significant effect of the 1990-2004 immigration on the average wage of U.S.-born workers overall, both in the short and in the long run. This positive average effect resulted from a positive effect on wages of all US-born workers with at least a high school degree and a small negative effect on wages of U.S born workers with no high school degree.
Keywords: F22; 330